Helping Dental Students Make Informed Decisions About Private Practice Employment Options in a Changing Landscape. Issue 12 (1st December 2015) - Badger, Gary R.; Fryer, Cheryl E.S.; Giannini, Peter J.; Townsend, Janice A.; Huja, Sarandeep
Abstract : According to the 2014 American Dental Education Association (ADEA) Survey of Dental School Seniors, 45.3% of new graduates planned to enter private practice immediately after graduation; of those, while 65% planned to become an associate dentist in a private practice, 28.3% intended to enter a corporate group practice—the only category that saw an increase over the previous year. Current trends indicate that the number of new graduates choosing to enter some form of private practice without further education will continue to remain high, due in large part to the need to repay educational debt. In light of these trends, the question that must be asked is whether dental schools are optimally preparing students to make informed decisions regarding future employment options in the changing dental practice landscape. This article argues that dental schools should review their curricula to ensure graduates are being prepared for this changing environment and the increased business pressures associated with dental practice. Important considerations in preparing dental students to be successful in the process of selecting a practice model are identified.